Effects of whole-body vibration exercise in patients with chronic kidney disease: a systematic review - Coelho-Oliveira, Ana Carolina; Silva, Adriana Biral de Jesus da; Braga, Suzana Sgarbi; Gama, Penha Valéria Lago da; Pessanha-Freitas, Juliana; Bezerra, Jani Cleria Pereira; Ferreira-Souza, Luiz Felipe; Moura-Fernandes, Márcia Cristina; Lacerda, Ana Cristina Rodrigues; Mendonça, Vanessa Amaral; Bachur, José Alexandre; Taiar, Redha; et al. (Disability and Rehabilitation, 2023)
Purpose Chronic kidney disease (CKD) is a clinical condition that promotes a decline in the overall health status of individuals affected, including parameters physical, functional, and psychosocial. This systematic review was conducted to assess effects of whole-body vibration exercise (WBVE) in individuals with CKD.Materials and methods It was conducted electronic searches in Pubmed, Embase, Scopus, Web of Science databases on May 2021. Records were identified and irrelevant studies were excluded based in eligibility criteria.Results Five studies were included with a mean methodological quality score of 9, considered high quality in PEDRo scale. The studies have shown that the WBVE intervention, when applied low intensity was well tolerated, and no adverse effects; was able to improve the motor performance and strength in frail people, which could benefit the prevention of falls events. However, did not improve the quality of life, and the heart rate variability; and not altered cardiorespiratory parameters.Conclusions WBVE intervention promotes a better response in parameters of the motor performance and muscular strength, and interaction bone-muscle. Nevertheless, more studies are needed with this intervention to improve physiological responses, and to understand your recommendation to prevent and reduce the complications and symptoms of the CKD, promoting an active life to these patients.Protocol study registration PROSPERO (CRD42020203295).IMPLICATIONS FOR REHABILITATIONChronic kidney disease (CKD) is a clinical condition that promotes a decline in the overall health status of individuals affected, including parameters physical, functional, and psychosocial.WBVE program possibility, of good acceptance, efficient as well tolerated by physically deconditioned patients who present difficulty to perform any type of exercise.WBVE protocol can promote changes in the patient with CKD lifestyle and benefits for this population because is an exercise without fatigue, impact, stress, or discomfort.
_eprint: https://doi.org/10.1080/09638288.2022.2037750
Keywords: Whole-body vibration; chronic disease; chronic kidney disease; mechanical vibration; renal disease